Molecular Epidemiology of Emerging Subvariants of the SARS-CoV-2 Omicron Lineage: A Cross-sectional Study from Himachal Pradesh, India - Priyanka Rao; Sunite A Ganju; Lata R Chandel (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) shows continuous genetic variation, resulting in the emergence of multiple viral lineages worldwide. These mutations can influence viral transmissibility, pathogenic potential, and immune escape, resulting in changed disease pattern. Genomic surveillance allows systematic tracking of viral evolution and circulating variants; thus, monitoring is essential for informed public health planning and clinical preparedness. Aim: To detect the emergence of variants of Omicron lineage in the hilly state of Himachal Pradesh, India. Materials and Methods: This cross-sectional study was conducted at the Shri Lal Bahadur Shastri Medical College, Mandi, Himachal Pradesh, India from January 2024 to June 2024. All the SARS-CoV-2 positive samples with Ct value ≤30 received across the state from the four Virus Research and Diagnostic Laboratories (VRDLs) of the state were included. Ribonucleic acid (RNA) extraction was performed using the Q-Line Molecular Viral RNA Extraction Kit, and Whole Genome Sequencing (WGS) was carried out on the Oxford Nanopore MinION platform. Consensus sequences were generated using Medaka and Nanopolish for variant identification and phylogenetic analysis. All demographic and clinical data, like age, sex, clinical presentation, and vaccination status, were recorded and tabulated in Microsoft Excel 2021. The study focused on genomic sequences generated, and the data were presented as numbers and percentages. Results: A total of 30 SARS-CoV-2 positive samples were received. Among SARS-CoV-2 positive cases, adult females constituted the highest proportion, 17 (56.7%), with most patients aged 19-60 years, 17 (56.7%), and the majority of samples originating from Shimla, 11 (36.7%). The study identified JN.1 sublineages in 19 (63.3%) as the predominant cause of infection. Most cases, 20 (66.7%) reported to the outpatient department. Mild symptoms such as fever and cough were seen in 7 (35%) cases. Even though 23 (76.7%) of cases were vaccinated with the COVID-19 vaccine, 10 (33.3%) required admissions. However, no mortality was reported. Conclusion: Tracking SARS-CoV-2 variants revealed the predominance of the JN.1 sublineage of Omicron with generally mild symptoms. Continuous genetic evolution of SARS CoV-2 highlights the need for robust, ongoing genomic surveillance integrated with epidemiological data to enable early detection of emerging variants and strengthen control strategies.